Effects of Short-Term Fasting on mRNA Expression of Ghrelin and the Peptide Transporters PepT1 and 2 in Atlantic Salmon (Salmo salar) - Del Vecchio, Gianmarco; Lai, Floriana; Gomes, Ana S.; Verri, Tiziano; Kalananthan, Tharmini; Barca, Amilcare; Handeland, Sigurd; Rønnestad, Ivar (Frontiers in Physiology, 2021)
Food intake is a vital process that supplies necessary energy and essential nutrients to the body. Information regarding luminal composition in the gastrointestinal tract (GIT) collected through mechanical and nutrient sensing mechanisms are generally conveyed, in both mammals and fish, to the hypothalamic neurocircuits. In this context, ghrelin, the only known hormone with an orexigenic action, and the intestinal peptide transporters 1 and 2, involved in absorption of dietary di- and tripeptides, exert important and also integrated roles for the nutrient uptake. Together, both are potentially involved in signalling pathways in control of food intake originating from different segments of the GIT. However, nothing is known about the role of different paralogues and their response to fasting. Therefore, after 3 weeks of acclimatization, 12 Atlantic salmon (Salmo salar) post-smolt were fasted for 4-days to explore the gastrointestinal response in comparison with fed control (n = 12). The analysis covered morphometric (weight, length, condition factor and wet content/weight fish %), molecular (gene expression variations) and correlation analyses. Such short term fasting is a common and recommended practice used prior to any handling in commercial culture of the species. There were no statistical differences in length and weight but a significant lower condition factor in the fasted group. Transcriptional analysis along the gastrointestinal segments revealed a tendency of down-regulation for both paralog genes slc15a1a and slc15a1b, and with significant lowered levels in the pyloric caeca for slc15a1a and in the pyloric caeca and midgut slc15a1b. No differences were found for slc15a2a and slc15a2b (except a higher expression of the fasted group in the anterior midgut), supporting different roles for slc15 paralogs. This represents the first report on the effects of fasting on slc15a2 expressed in GIT in teleosts. Transcriptional analysis of ghrelin splicing variants (ghrl-1 and ghrl-2) showed no difference between treatments. However, correlation analysis showed that mRNA expression for all genes (restricted to segment with the highest levels) were affected by the residual luminal content. Overall, the results show minimal effects of 4-days of induced fasting in Atlantic salmon, suggesting that more time is needed to initiate a large GIT response.